The Judiciary in Governance: Understanding the Juridical Nature and Function of the Constitutional Court of Indonesia - Mendy, Ousu; Sarr, Ebrima (Journal of Indonesian Constitutional Law, 2025)
The Constitutional Court of Indonesia as a state institution is a constitutional edict established in Article 24C of the 1945 Constitution of Indonesia. It is an act of commitment to good governance in all its dimensions. This research examines the role this court plays in promoting governance in Indonesia through its engagements with other state institutions. This research uses a doctrinal or normative legal research method to reflect on the function of this court. This court has a strong commitment towards checks and balances in order to guarantee constitutional order and supremacy, although the finality of this supremacy should not preclude constitutional dialogue. The political, democratic, and social life of Indonesia has become more vibrant as a result of the establishment of this court. This development in the history of the country’s constitutional law is premised on the ground that, building a constitutional democratic state in a country requires improving its legal frameworks. One of the initiatives is to create a framework that questions the constitutionality or validity of laws when they have reservations about them. The Constitutional Court mechanism does that. It is a court with sui generis jurisdiction in determining constitutional matters including most controversial issues of election petitions and presidential impeachment. Therefore, it is sufficient to posit that this court forms the bedrock of good governance and democratisation in Indonesia where acts of institutions and individuals are subject to the scrutiny of the constitution thereby, validating the longstanding cliché of “government of laws and not of men”.